أثر استخدام البرمجة بالرمز الشريطي Barcode في إكساب طلبة المرحلة الابتدائية مهارات برمجة الروبوت إديسون Edison. - مهند يوسف عبد ال&#1602 (Hebron University Research Journal (Humanities), 2025)
The research aimed to identify the effect of using barcode programming on primary school students' acquisition of Edison robot programming skills. The researcher used the semi-experimental design based on the one-group design with two measurements, before and after. The sample of the study consisted of (13) students from the fifth grade at the Directorate of Education in western Gaza. The study tool consisted of a cognitive test and a note card to measure students’ performance and verify the acquisition of Edison robot programming skills. The results revealed statistically significant differences at the level of α=0.01 between the medians of the scores of the students of the experimental group in (cognitive aspect test, and the note card for Edison robot programming skills) before and after the application in favor of the post application. The results also indicated a very significant effect of using barcode programming in acquiring robot programming skills. The research recommended several recommendations, including conducting similar research on other age groups.